2007
DOI: 10.1097/01.sla.0000250418.14359.31
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Vancomycin Controls Methicillin-resistant Staphylococcus Aureus Endemicity in an Intensive Care Burn Unit

Abstract: Enteral vancomycin is an effective and safe method to control MRSA in intensive care burn units without VRE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 61 publications
1
31
0
3
Order By: Relevance
“…Two recent randomized controlled trials demonstrated that SDD does not increase resistance but actually reduces antibiotic resistance [4,5]. Moreover five long-term SDD observational studies monitored antimicrobial resistance between 2 and 7 years, and reported that bacterial resistance associated with SDD was not a clinical problem [7][8][9][10][11]. These studies have some potential weaknesses: one study was a retrospective case-control study, two studies assessed the percentage of antibiotic-resistant isolates instead of the incidence of patients who acquired antibiotic-resistant bacteria (ARB) [9,10], two studies specifically estimate the efficacy and safety of enteral vancomycin to eradicate oxacillin-resistant Staphylococcus aureus (ORSA) [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent randomized controlled trials demonstrated that SDD does not increase resistance but actually reduces antibiotic resistance [4,5]. Moreover five long-term SDD observational studies monitored antimicrobial resistance between 2 and 7 years, and reported that bacterial resistance associated with SDD was not a clinical problem [7][8][9][10][11]. These studies have some potential weaknesses: one study was a retrospective case-control study, two studies assessed the percentage of antibiotic-resistant isolates instead of the incidence of patients who acquired antibiotic-resistant bacteria (ARB) [9,10], two studies specifically estimate the efficacy and safety of enteral vancomycin to eradicate oxacillin-resistant Staphylococcus aureus (ORSA) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover five long-term SDD observational studies monitored antimicrobial resistance between 2 and 7 years, and reported that bacterial resistance associated with SDD was not a clinical problem [7][8][9][10][11]. These studies have some potential weaknesses: one study was a retrospective case-control study, two studies assessed the percentage of antibiotic-resistant isolates instead of the incidence of patients who acquired antibiotic-resistant bacteria (ARB) [9,10], two studies specifically estimate the efficacy and safety of enteral vancomycin to eradicate oxacillin-resistant Staphylococcus aureus (ORSA) [7,8]. The impact of potential confounding factors such as the prevalence of ARB on intensive care unit (ICU) admission, the frequency of sampling, and intrinsic factors associated with acquisition of resistance has been only evaluated in two trials [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…More novel treatment modalities for intestinal MRSA elimination to control transmission or subsequent infections, e.g., using oral vancomycin, have been described merely in uncontrolled or observational studies. Oral vancomycin treatment results were reported that showed that the eradication of MRSA intestinal carriage by enteral vancomycin in subsets of adult ICU patients [58][59][60] as well as in pediatric patients [61,62] was effective, but had limited effect on the prevention of transmission. The results from prospective controlled studies of intestinal MRSA decolonization are urgently awaited.…”
Section: Eradication Of Intestinal Carriagementioning
confidence: 99%
“…Enteral vancomycin may be effective in reducing MRSA infection when included in the SDD protocol, prompting suggestions that it should be used as part of SDD in MRSA-endemic units. A recent study from Spain comparing MRSA rates in burns patients receiving SDD without vancomycin for a 5-year period to rates in a subsequent 4-year period when vancomycin was added to the SDD regimen demonstrated a significant reduction in MRSA acquisition in the latter period [19]. Other studies have demonstrated a reduction in MRSA acquisition [20,21] and control of an MRSA outbreak [22] with vancomycin-containing regimens.…”
Section: Discussionmentioning
confidence: 99%